Vivência da fecundidade por famílias capixabas: estudo intergeracional - Wanderley, Thaís Caus (2009)
The social and affective roles experienced by family members are themes that have been discussed in many areas of human science, including the Psychology. However, it seems to exist a tendency in focusing only on the aspects of motherhood, fatherhood, or even other internal dynamics, while the structuring role played by the child in the family seems to be neglected. In this direction, the present study sought to understand, through the study of the experience of fertility in the family environment during the 20th century, the role that the child has been playing in capixabas families. It was also the objective of this research to study the raising of children during the 20th century; relate fertility to the matters of gender and conjugality; verify practices of contraception and family planning used during the 20th century, as well as their acceptance; trying to understand in which place children are in the family organization. To accomplish that was done an intergenerational study, comparing three generations of six different families, reaching a total of eighteen participants. It was done a gender distinction so comparisons could be made. Therefore, were invited to participate of this research three groups of women – daughters, mothers and grandmothers – and three groups of men – sons, fathers and grandfathers, each group being composed by the same family. The instrument used in the data gathering was a semi structured individual interview, so the information could be gathered in depth. Were constructed individual narratives from the units of meaning that were related to this study in the participant’s speech. The data analysis was qualitative based on the narratives, comparing generations so an understanding could be reached from the experiences lived by the Brazilian families about fertility during the 20th century. The results showed that the child continues to be essential to the construction of the family, even being in different ways among the generations. The model of nuclear family is still used as a reference and the family has great social value, even though were found expressive changes in the ways of raising children, in the relations of gender and conjugality, in the use of contraceptives and family planning. All those elements were studied related to the history of the 20th century, which allowed the confirmation that the family practices affect and are affected by the social circumstances they belong.